A regulatory mutant on TRIM26 conferring the risk of nasopharyngeal carcinoma by inducing low immune response - Xiao‐Ming Lyu; Xiao‐Wei Zhu; Manli Zhao; Xian‐Bo Zuo; Zhong‐Xi Huang; Xiao Liu; Tao Jiang; Xue‐Xi Yang; Xin Li; Xiao‐Bing Long; Jian‐Guo Wang; Jin‐Bang Li; et al. (Cancer Medicine)
Abstract The major histocompatibility complex (MHC) is most closely associated with nasopharyngeal carcinoma (NPC), but the complexity of its genome structure has proven challenging for the discovery of causal MHC loci or genes. We conducted a targeted MHC sequencing in 40 Cantonese NPC patients followed by a two‐stage replication in 1065 NPC cases and 2137 controls of Southern Chinese descendent. Quantitative RT‐PCR analysis (qRT‐PCR) was used to detect gene expression status in 108 NPC and 43 noncancerous nasopharyngeal (NP) samples. Luciferase reporter assay and chromatin immunoprecipitation (ChIP) were used to assess the transcription factor binding site. We discovered that a novel SNP rs117565607_A at TRIM26 displayed the strongest association (OR = 1.909, Pcombined = 2.750 × 10−19). We also observed that TRIM26 was significantly downregulated in NPC tissue samples with genotype AA/AT than TT. Immunohistochemistry (IHC) test also found the TRIM26 protein expression in NPC tissue samples with the genotype AA/AT was lower than TT. According to computational prediction, rs117565607 locus was a binding site for the transcription factor Yin Yang 1 (YY1). We observed that the luciferase activity of YY1 which is binding to the A allele of rs117565607 was suppressed. ChIP data showed that YY1 was binding with T not A allele. Significance analysis of microarray suggested that TRIM26 downregulation was related to low immune response in NPC. We have identified a novel gene TRIM26 and a novel SNP rs117565607_A associated with NPC risk by regulating transcriptional process and established a new functional link between TRIM26 downregulation and low immune response in NPC.